The Effectiveness Analysis of Using Angle Puzzle Tools on the Achievement of Students’ Learning Outcomes - I Nyoman Sudyana; Hartin Kurniawati; Rachmat Susanto; Irma Maria Dulame; Antonius Rino Vanchapo (Departement of Mathematics Education, 2023)
The purpose of this study is to determine whether corner puzzle props are useful in enhancing student learning results. The study was conducted through experimental research using a posttest-only control design. The participants of the study were students, with class A being the experimental group and class B as the control group. The data collection method employed in this study was documentation and testing. The results of the analysis of academic performance using corner puzzle props indicated a significant improvement in the average academic performance of the experimental group, which was 69.83, compared to the control group, which was 62.07. The data was analyzed using a difference test (t test) on the right side. The research on academic performance revealed that the t-count was higher than the t-table. This implies that the average academic performance of students in class A (the experimental group) who were taught using corner puzzle props was greater than or equal to that of students who were not taught using corner puzzle props.